Análise e descrição da língua Wayanã - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1993)
The present work aims to develop a study about the Wayanã language, which is spoken by the indigenous group of the same name. The Wayanã reside in villages located along the Paru River of East Citaré, north of Pará. Classified as karib language is, among the languages of this family, one of the least documented. Data collection was performed through the recording of words and interviews with Wayanã informants at the Indian House in Icoaraci and at the FUNAI Regional Post in Macapá. Thus, with the transcription and the consequent analysis of the data, it was possible to establish a preliminary phonological picture of the language, as well as the observation of certain phenomena at the level of morphology, such as the idea of possession that the language expresses.
Analysis and description of the Wayanã language
Keywords: Língua; Wayanã; CNPQ::CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA